On-Field Signs Predict Future Acute Symptoms After Sport-Related Concussion: A Structural Equation Modeling Study. (8th January 2018) - Brett, Benjamin L.; Kuhn, Andrew W.; Yengo-Kahn, Aaron M.; Jeckell, Aaron S.; Solomon, Gary S.; Zuckerman, Scott L.
Abstract: Objectives: This study investigated the relationship between on-field, objective signs immediately following sport-related concussion and self-reported symptom endorsement within 1 day post injury.Methods: A retrospective case series of 237 concussed high school athletes was performed. On-field signs were evaluated immediately post injury. Self-reported symptoms (2 clusters) were collected within 1 day post injury. A two-step structural equation model and follow-up bivariate regression analyses of significant on-field signs and symptom clusters were performed.Results : Signs of immediate memory, β=0.20, p =.04, and postural instability, β=0.19, p < .01, significantly predicted a greater likelihood of endorsing the cognitive-migraine-fatigue symptom cluster within 1 day post injury. Regarding signs correlated with specific symptoms, immediate memory was associated with symptoms of trouble remembering, χ 2 =37.92, p < .001, odds ratio (OR)=3.89 (95% confidence interval (CI) [2.47, 6.13]), and concentration difficulties, χ 2 =10.84, p =.001, OR=2.13 (95% CI [1.37, 3.30]). Postural instability was associated with symptom endorsement of trouble remembering, χ 2 =12.08, p < .001, OR=1.76 (95% CI [1.29, 2.40]).Conclusions: Certain post-concussion on-field signs exhibited after injury were associated with specific symptom endorsement within 1 day post injury. Based on these associations, individualized education-based interventions and academic accommodations may help reduce unanticipated worry from parents, students, and teachers following a student-athlete's sport-related concussion, especially in cases of delayed onset symptoms. ( JINS, 2018, 24, 476–485)